2019
DOI: 10.1007/978-3-319-92735-0_45
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the “Deep Reef Refuge” Hypothesis: A Conceptual Framework to Characterize Persistence at Depth

Abstract: The rapid deterioration of coral reefs worldwide has led to a growing interest in identifying areas that can offer protection against adverse conditions including coral reef communities at intermediate (~15-30 m) and mesophotic (≥ 30 m) depths. However, various concepts regarding the protective potential of deeper coral reef communities, and subsequent roles in overall reef resilience and persistence, remain poorly defined. Herein, we organize these ideas into an initial conceptual framework, and review for sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 102 publications
(177 reference statements)
0
72
0
2
Order By: Relevance
“…Furthermore, persistent organic pollutants such as PCBs can have detrimental effects on ecological systems such as MCEs owing to their high toxicity, lipophilic properties, and widespread dispersal in the marine environment (Jafarabadi et al, 2019a(Jafarabadi et al, , 2019b. These threats and others (e.g., heatwaves, warming and acidification) discussed in this manuscript may undermine the ability of MCEs to act as a depth refugium or depth resilience areas (sensu Bongaerts and Smith, 2019).…”
Section: Limited Potential Refuge Against Human Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, persistent organic pollutants such as PCBs can have detrimental effects on ecological systems such as MCEs owing to their high toxicity, lipophilic properties, and widespread dispersal in the marine environment (Jafarabadi et al, 2019a(Jafarabadi et al, , 2019b. These threats and others (e.g., heatwaves, warming and acidification) discussed in this manuscript may undermine the ability of MCEs to act as a depth refugium or depth resilience areas (sensu Bongaerts and Smith, 2019).…”
Section: Limited Potential Refuge Against Human Effectsmentioning
confidence: 96%
“…There is little empirical evidence to sustain that areas that provided depth refuge (short-term buffering or shelter against a particular disturbance episode) scale to refugia. In fact, the increasing frequency and severity of global impacts (warming and heatwaves) and regional human disturbances (e.g., pollution and fishing activities) cast doubt on the ability of MCEs to provide protection over the long-term (over multiple disturbances) (Bongaerts and Smith, 2019).…”
Section: Limited Potential Refuge Against Human Effectsmentioning
confidence: 99%
“…Despite these differences, many scleractinian species in the Tropical Western Atlantic (TWA) co-occur on both shallow reefs and MCEs (as much as 25-40%; Bongaerts et al, 2010Bongaerts et al, , 2017. Due in part to the species overlap with shallow reefs, MCEs are hypothesized to be potential refuges for shallow reefs (i.e., the Deep Reef Refugia Hypothesis; Glynn, 1996;Bongaerts et al, 2010;Lesser et al, 2018;Bongaerts and Smith, 2019). Multiple studies have examined the potential for "reseeding" of shallow reefs with larvae from MCE coral counterparts using molecular methods to quantify levels of genetic connectivity between these habitats (Brazeau et al, 2013;Bongaerts et al, 2017;Studivan and Voss, 2018;Eckert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that MCEs can be divided into two distinct zones: an upper mesophotic one, between 30-60 m; and a lower one, below 60 m (Lesser et al, 2010;Brazeau et al, 2013;Bongaerts et al, 2015). It has also been broadly suggested that deeper reefs are less affected by direct climate-induced disturbances compared to shallow reefs (Glynn, 1996;Hughes and Tanner, 2000;Bak et al, 2005;Laverick and Rogers, 2017;Baird et al, 2018) and, therefore, the occurrence of thriving MCE communities has led to the "deep-reef refuge hypothesis" (DRRH: Bongaerts et al, 2010Bongaerts et al, , 2019. It is hypothesized that MCEs may function as a refuge for certain organisms during periods of stress in the shallow waters and, in the aftermath, act as a potential source of propagules for recovery of the disturbed shallow communities (e.g., Kahng et al, 2014;Bongaerts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%